Analyzing Student Career Development at State Middle School 35 Medan Based on Life Span Theory, Super Theory - Yohana Kezzia Br Tarigan Cinta Wulandhara Lubis; Cinta Wulandhara Lubis Yohana Kezzia Br Tarigan; Lia Erika Yohana; Anggi Agustia Lubis Yohana; Dea Nisya Nabila Yohana (Asesment : Journal Of Counseling Guidance, 2023)
The research was conducted to analyze and determine the career development of students at SMP Negeri 35 Medan based on the Life Span Theory and super Theory. Here, the research subjects were 30 students at SMP Negeri 35 Medan. This research uses primary data sources, which are obtained directly by researchers. This research uses a questionnaire method, so the data source is students at SMP Negeri 35 Medan. Data is analyzed quantitatively, which is systematic scientific research on parts and phenomena and the causality of their relationships. Quantitative research aims to develop and use mathematical models, theories, and/or hypotheses related to a phenomenon. From the results of the research that has been carried out, it is clear that the students who are the research subjects can be seen from the results of the questionnaire answers given to this question. In the twelfth question, whether you are confident and easily mix with others. There were 33.3% who answered Yes and 66.7% answered No. A problem found among students was a lack of self-confidence. This is related to self-concept with the theory of career selection and development according to the Life Span Theory and super Theory regarding (child and adolescent development). So that self-concept is a part and description of the whole self, it can be concluded that a lack of self-confidence can affect an individual's self-concept later.